2007
DOI: 10.1002/ijc.22891
|View full text |Cite
|
Sign up to set email alerts
|

Consistent expression of the stem cell renewal factor BMI‐1 in primary and metastatic melanoma

Abstract: Stem cell-like cells have recently been identified in melanoma cell lines, but their relevance for melanoma pathogenesis is controversial. To characterize the stem cell signature of melanoma, expression of stem cell markers BMI-1 and nestin was studied in 64 cutaneous melanomas, 165 melanoma metastases as well as 53 melanoma cell lines. Stem cell renewal factor BMI-1 is a transcriptional repressor of the Ink4a/Arf locus encoding p16 ink4a and p14Arf . Increased nuclear BMI-1 expression was detectable in 41 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 54 publications
0
67
1
Order By: Relevance
“…S1a,b and Supplementary Table S1). Furthermore, extending studies by others 10-14 , we analyzed expression of SOX10 in a large set of human primary melanomas and melanoma metastases 15 . We found that the vast majority of all melanoma samples displayed nuclear SOX10 staining (Fig.…”
mentioning
confidence: 84%
“…S1a,b and Supplementary Table S1). Furthermore, extending studies by others 10-14 , we analyzed expression of SOX10 in a large set of human primary melanomas and melanoma metastases 15 . We found that the vast majority of all melanoma samples displayed nuclear SOX10 staining (Fig.…”
mentioning
confidence: 84%
“…In humans, Bmi-1 plays an essential role in maintaining the self-renewal of normal and malignant human mammary stem cells (13). Meanwhile, Bmi-1 is also dysregulated in various human malignant neoplasms (14)(15)(16)(17)(18)(19). Previously, we reported that upregulation of Bmi-1 correlates with invasion of nasopharyngeal carcinomas (NPCs) and poor prognosis in patients (20).…”
Section: Introductionmentioning
confidence: 99%
“…Markers of melanocytic stem cells have been recently described (16,17), including nestin, an intermediate filament, which is expressed mainly in the cytoplasm of neuroepithelial stem cells (18,19) and in endothelium of growing blood vessels (20,21) but not in differentiated cells in parallel to loss of immunoreactivity to this protein (22). CD133 (human prominin-1/AC133), is another stem cell marker, a transmembrane glycoprotein that is expressed on hematopoietic stem cells, endothelial progenitor cells, and dermalderived stem cells capable of differentiating into neural cells (23,24).…”
Section: Introductionmentioning
confidence: 99%